Analisis Penerapan Ekonomi Sirkular Pada UMKM F&B Di Sekitar Medan - Siregar, Mufti Al Mumtaz; Karo Karo, Robby Adriano; Ardiansyah, Reza Restu; Nasution, Yenni Samri Juliati (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to analyze the implementation of circular economy in Micro, Small, and Medium Enterprises (MSMEs) in the Food & Beverage (F&B) sector. The focus of the research is on the implementation of circular economy practices that include waste management, use of sustainable raw materials, environmentally friendly packaging, energy and water efficiency, and food waste reduction strategies. The research method used a descriptive quantitative approach with a research instrument in the form of a questionnaire distributed through Google Form.